A Survey of Smart Contracts: Security and Challenges - Md. Ratul Amin, Megat F. Zuhairi, Md. Nazmus Saadat (International Journal of Advanced Science and Technology, 2020)
To date, a lot of information are processed and stored online. As such, an efficient method to secure and enhance the trustworthiness of data is needed. A particular technology, inspired by the need to remove middle-man and increase transparency of online transaction, is the blockchain technology. The inherent nature of such technology is the distributed ledger system. In conventional method, which is centrally managed, the third party i.e. banks, insurance company, government agencies, controls business dealing between customers and providers. Much of the transactions incur charges. It is because the third party provides some degree of assurance to the transactions and provide recourse to users when a deal is not honoured. Additionally, transparency is absence in the traditional method, leading to opportunity for fraudulence activity. The data security of blockchain gained to unchangeable by the cryptography algorithm. By the virtue of blockchain, notable challenges of conventional technologies have decoded. Keywords: Blockchain, crypto-hash, Merkle tree, smart contract, security.